(002) crystal face oriented zinc powder negative electrode material as well as preparation method and application thereof
Through ball milling and annealing treatment technology, a zinc powder negative electrode material with a crystal plane orientation was prepared, which solved the problems of zinc dendrites growth and unstable battery performance, and significantly improved the cycle stability and energy density of the battery.
Patent Information
- Application Number
- CN202411543375.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing zinc powder negative electrode materials of the current aqueous zinc ion battery are prone to problems such as hydrogen evolution, corrosion and zinc dendrites during charging and discharging, resulting in unstable battery performance.
By mixing zinc powder with grinding agent and then performing ball milling treatment in an inert atmosphere, the form and crystal surface structure of zinc powder are optimized to achieve the preparation of zinc powder negative electrode material with crystal surface orientation (002).
This method effectively inhibits the formation of zinc dendrites, improves the cycle stability and energy density of zinc powder negative electrode materials, and extends the service life of the battery.
Smart Images

Figure CN119407158A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to a zinc powder negative electrode material with a (002) crystal plane orientation, and a preparation method and application thereof. Background Art
[0002] Aqueous zinc-ion batteries have attracted much attention in the field of energy storage due to their excellent safety, economy and wide distribution of zinc resources. However, in the process of large-scale commercialization, zinc negative electrodes still face problems such as zinc dendrite growth, hydrogen evolution and corrosion that need to be overcome. At present, research on negative electrodes of aqueous zinc-ion batteries is mostly focused on the interface protection of zinc foil negative electrodes. These strategies usually use thicker zinc foil to achieve better cycle performance, but this sacrifices the utilization of zinc metal, resulting in a higher N / P ratio and reducing the energy density of the battery. In addition, due to the unevenness of the stripping process, the zinc foil, which has both negative electrode and current collector functions, may shatter and break, further affecting battery performance.
[0003] In contrast, zinc powder has the advantages of low cost, good processability and excellent adjustability. In particular, zinc powder has the advantage of adjustable dosage, which can well control the N / P ratio of the battery. However, zinc powder with a larger specific surface area is more prone to problems such as hydrogen evolution and corrosion due to the exposure of higher active sites. In addition, during the charge and discharge process, small zinc powder particles preferentially dissolve and deposit around large zinc particles, which can easily cause the growth of zinc dendrites and increase the risk of battery short circuit.
[0004] Therefore, developing a zinc powder negative electrode preparation technology that can effectively inhibit zinc dendrite growth and improve the cycle stability of zinc negative electrode is crucial to improving the overall performance of aqueous zinc ion batteries. The (002) crystal plane of zinc is considered to be an ideal choice for inhibiting dendrite growth and side reactions due to its low surface energy and the most compact stacking morphology. At present, the methods for improving the texture strength of the (002) crystal plane mainly include electrochemical deposition, chemical etching and roller pressing, but these methods usually have complicated preparation processes and are mainly used for the modification of zinc foil. Realizing the preferential exposure of the (002) crystal plane in zinc powder negative electrode materials is still the main challenge facing current technological development. Summary of the invention
[0005] The purpose of the present invention is to provide a (002) crystal plane oriented zinc powder negative electrode material and a preparation method and application thereof, so as to solve the technical problem that the preparation process of the existing zinc powder negative electrode material is complicated when the overall performance of the zinc ion battery is improved.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation, comprising the following steps: After mixing zinc powder and a grinding aid, ball milling is performed in an inert atmosphere to obtain a mixed powder; The mixed powder is annealed in an inert atmosphere to obtain a zinc powder negative electrode material with a (002) crystal plane orientation.
[0007] Furthermore, the ball-to-material ratio of the ball milling treatment is (4-10):1; the rotation speed of the ball milling treatment is 200-500 r / min, and the time is 4-16 h.
[0008] Furthermore, the grinding aid is one or more of stearic acid, calcium stearate, zinc stearate, polyvinyl alcohol and polyethylene glycol.
[0009] Furthermore, the amount of the grinding aid is 1-10wt% of the mass of the zinc powder.
[0010] Furthermore, the zinc powder is spherical zinc powder.
[0011] Furthermore, the inert atmosphere is one of a nitrogen atmosphere, a helium atmosphere or an argon atmosphere.
[0012] Furthermore, the parameters of the annealing treatment are: The heating rate is 5~10℃ / min, the annealing temperature is 300~415℃, and the annealing time is 5~16h.
[0013] The invention also discloses a zinc powder negative electrode material with (002) crystal plane orientation prepared by the preparation method.
[0014] The invention also discloses the application of the zinc powder negative electrode material with (002) crystal plane orientation in aqueous zinc ion batteries.
[0015] Furthermore, compared with traditional zinc powder negative electrode materials, the cycle life of the aqueous zinc ion battery is increased by two to three times.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation. The method adopts zinc powder as a raw material, optimizes the morphology and crystal plane structure of the zinc powder by controlling the processes of ball milling and annealing, induces the formation of a zinc powder negative electrode material with a (002) crystal plane orientation, effectively inhibits the formation of zinc dendrites, and presents a more compact stacking morphology. The method has a simple and easy preparation process, low cost, mild operating conditions, is easy to realize large-scale production, is conducive to reducing production costs, and has high practicality.
[0017] Furthermore, the method disclosed in the present invention uses zinc powder as the negative electrode material, which significantly improves the utilization rate of zinc compared to the traditional zinc foil negative electrode, and helps to improve the energy density of the battery. In addition, after the morphology and structure of the zinc powder are optimized by the ball milling and annealing process of the present invention, more uniform zinc ion embedding and extraction can be achieved, thereby giving full play to the potential and advantages of zinc powder in aqueous zinc ion batteries.
[0018] The present invention also discloses a zinc powder negative electrode material with a (002) crystal plane orientation prepared by the above-mentioned preparation method. The preferentially exposed (002) crystal plane not only has a lower surface energy, but also effectively inhibits the formation of zinc dendrites, thereby reducing the risk of battery short circuit and improving the cycle stability of the battery; the optimized crystal plane structure can also effectively inhibit side reactions, reduce hydrogen evolution and corrosion, improve the reversibility of the battery, and extend the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a morphological characterization diagram of the zinc powder negative electrode material prepared in Examples 1 to 3 and Comparative Example 1; Wherein: A-Comparative Example 1; B~D-Example 1~Example 3; Figure 2 It is a crystal structure characterization diagram of the zinc powder negative electrode material prepared in Examples 1 to 3 and Comparative Example 1; Figure 3 This is a cycle data diagram after assembling a symmetrical battery with the zinc powder negative electrode materials prepared in Examples 1 to 3 and Comparative Example 1; Wherein: A-Comparative Example 1; B~D-Example 1~Example 3; Figure 4 This is a morphological characterization diagram of the zinc powder negative electrode material after the zinc powder negative electrode material prepared in Example 3 and Comparative Example 1 was assembled into a symmetrical battery and cycled for 50 hours; Wherein: A-Comparative Example 1; B-Example 3; Figure 5 This is a graph showing the cycle data after assembling a zinc-copper asymmetric battery with the zinc powder negative electrode materials prepared in Example 3 and Comparative Example 1; Wherein: A-time voltage curve; B-Coulomb efficiency diagram; DETAILED DESCRIPTION In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] The present invention provides a method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation, comprising the following steps: Step 1: Mix spherical zinc powder with one or more grinding aids, and while adding the mixture into a ball mill, introduce inert gas into the mill to prevent oxidation of the metal powder; Step 2: ball milling the mixture obtained in step 1 in a ball mill to obtain mixed powder to optimize the morphology of zinc powder; Step 3: placing the mixed powder obtained in step 2 in a tubular furnace protected by inert gas for annealing to optimize the crystal surface structure of the zinc powder and obtain the target product.
[0025] Preferably, in step 1, the grinding aid is one or more of stearic acid, calcium stearate, zinc stearate, polyvinyl alcohol and polyethylene glycol.
[0026] Preferably, in step 1, the amount of the grinding aid is 1-10wt% of the mass of the spherical zinc powder; and the inert gas introduced is one of nitrogen, helium or argon.
[0027] Preferably, in step 2, the ball-to-material ratio for ball milling is 4-10:1, the rotation speed of the ball mill is 200-500 r / min, and the ball milling time is 4-16 h.
[0028] Preferably, in step 3, the inert gas is one of nitrogen or argon; the parameters of the annealing treatment are: a heating rate of 5-10°C / min, an annealing temperature of 300-415°C, and an annealing time of 5-16h.
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0031] Example 1 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh 2 wt% (i.e. 0.132 g) of stearic acid as a grinding aid, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 4 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace and set the heating rate to 10°C / min. When the temperature rises to 415°C, maintain this temperature for annealing. The annealing time is set to 5h. During the non-treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0032] Example 2 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh 2 wt% (i.e. 0.132 g) of stearic acid as a grinding aid, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 8 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace and set the heating rate to 10°C / min. When the temperature rises to 415°C, maintain this temperature for annealing. The annealing time is set to 5h. During the non-treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0033] Example 3 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh 2 wt% (i.e. 0.132 g) of stearic acid as a grinding aid, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 12 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace and set the heating rate to 10°C / min. When the temperature rises to 415°C, maintain this temperature for annealing. The annealing time is set to 5h. During the non-treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0034] Example 4 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh 4 wt% (i.e. 0.264 g) of stearic acid as a grinding aid, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 12 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace and set the heating rate to 10°C / min. When the temperature rises to 415°C, maintain this temperature for annealing. The annealing time is set to 5h. During the non-treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0035] Example 5 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh 2 wt% (i.e. 0.132 g) of stearic acid as a grinding aid, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 12 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace, set the heating rate to 10°C / min, and when the temperature rises to 300°C, maintain this temperature for annealing. The annealing time is set to 5h. During the non-treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0036] Example 6 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh 2 wt% (i.e. 0.132 g) of stearic acid as a grinding aid, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 12 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace and set the heating rate to 10°C / min. When the temperature rises to 415°C, maintain this temperature for annealing. The annealing time is set to 5h. During the non-treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0037] Example 7 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh zinc stearate as a grinding aid according to 2 wt% (i.e. 0.132 g) of the mass of the spherical zinc powder, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 200 r / min, and set the ball milling time to 4 h to obtain a mixed powder; Step 3: The obtained mixed powder is transferred to a tube furnace, and the heating rate is set to 5°C / min. When the temperature rises to 415°C, this temperature is maintained for annealing. The annealing time is set to 5h. During the treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with (002) crystal plane orientation is obtained. Example 8 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh 2 wt% (i.e. 0.132 g) of zinc stearate as a grinding aid, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce nitrogen into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 16 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace and set the heating rate to 10°C / min. When the temperature rises to 415°C, maintain this temperature for annealing. The annealing time is set to 16 hours. During the non-treatment process, argon gas is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0038] Example 9 A method for preparing a zinc powder negative electrode material with a (002) crystal plane orientation comprises the following steps: Step 1: Take 6.6 g of commercially available spherical zinc powder, weigh polyvinyl alcohol as a grinding aid according to 2 wt% (i.e. 0.132 g) of the mass of the spherical zinc powder, mix the spherical zinc powder and stearic acid evenly, add them into a ball mill, and introduce argon gas into the ball mill to prevent oxidation of the metal powder; Step 2: Place the ball mill containing the mixture into a ball mill with a ball-to-material ratio of 4:1, set the ball mill speed to 500 r / min, and set the ball milling time to 16 h to obtain a mixed powder; Step 3: Transfer the obtained mixed powder to a tube furnace, set the heating rate to 10°C / min, and when the temperature rises to 415°C, maintain this temperature for annealing. The annealing time is set to 16 hours. During the non-treatment process, helium is continuously introduced to maintain an inert atmosphere. After cooling, a zinc powder negative electrode material with a (002) crystal plane orientation is obtained.
[0039] Comparative Example 1 This comparative example directly uses untreated commercially available zinc powder.
[0040] In order to characterize the morphology and crystal structure of the zinc powder negative electrode material of the present invention, the zinc powders obtained in Examples 1 to 3 and Comparative Example 1 were analyzed using scanning electron microscopy (SEM) and X-ray diffraction (XRD).
[0041] Through SEM observation, Figure 1 As shown in FIG. 1 , the zinc powder in comparative example 1 is spherical in shape (marked as A). The zinc powders obtained in Examples 1 to 3 all exhibit flaky morphology (marked as B, C, and D). As the ball milling time increases, the degree of flaking becomes more significant, and the flaky structure becomes thinner and finer. The XRD analysis results are shown in FIG. Figure 2 As shown. The untreated zinc powder in Comparative Example 1 shows diffraction peaks at 36°, 38° and 43°, corresponding to the characteristic peaks of the (002), (100) and (101) crystal planes of crystalline zinc, respectively. The relative diffraction intensity of the zinc powder obtained in Examples 1 to 3 at the (002) / (100) crystal plane is significantly improved compared with that in Comparative Example 1, which indicates that the method of the present invention can effectively promote the preferential exposure of the (002) crystal plane. In addition, with the increase of ball milling time, the diffraction intensity of the (002) crystal plane is also correspondingly enhanced, confirming the regulatory effect of ball milling on crystal plane orientation.
[0042] Performance Test 1 The zinc powder negative electrode material obtained in Examples 1 to 3 and Comparative Example 1 was compounded with a conductive agent and a binder, and then an organic solvent was added to obtain a slurry, which was then scraped onto a copper foil and dried to form a pole piece. The conductive agent is carbon black, the binder is PVDF, the mass ratio of the zinc powder negative electrode material, the conductive agent, and the binder is 8:1:1, and the organic solvent is NMP. The drying conditions are preferably a temperature of 80°C and a time of 12h. The pole piece after drying was punched into a circular pole piece with a diameter of 12 mm, and a 2 M zinc sulfate solution was used as the electrolyte, and a glass fiber filter paper was used as a diaphragm to assemble a zinc-zinc symmetrical battery (positive and negative electrodes are the same), and a constant current charge and discharge test was performed.
[0043] A total of three groups of Zn|Zn symmetrical batteries assembled from Examples 1 to 3 and one group of Zn|Zn symmetrical batteries assembled from Comparative Example 1 were heated at 2 mA cm -2 The current density is 2 mAh cm -2 The surface capacity (zinc utilization rate is 30%) was cycled, and the sudden change of battery overpotential was used as the criterion for short circuit. Figure 3 As shown, the Zn|Zn symmetric battery of Comparative Example 1 short-circuited after running for about 30 hours, and the Zn|Zn symmetric battery of Example 3 short-circuited after running for about 130 hours.
[0044] Further observation of the surface of the zinc negative electrode after cycling, such as Figure 4As shown in Figure A, the surface dendrite growth of the zinc negative electrode of the Zn|Zn symmetric battery assembled in Comparative Example 1 is serious after cycling, while the surface of the zinc negative electrode of the Zn|Zn symmetric battery assembled in Example 3 is relatively smooth and has a dense structure after cycling; this indicates that the crystal plane regulation method provided by the present invention can effectively inhibit the formation of zinc dendrites and significantly improve the cycle performance of the zinc powder negative electrode; in addition, by comparing the results of Examples 1 to 3, it can be found that increasing the ball milling time can significantly improve the cycle stability of the zinc powder negative electrode, which is also consistent with the XRD results, confirming the effectiveness of crystal plane regulation.
[0045] Performance Test 2 The zinc powder negative electrode material obtained in Examples 1 to 3 and Comparative Example 1 is compounded with a conductive agent and a binder, and then an organic solvent is added to obtain a slurry, which is then scraped onto a copper foil and dried to form an electrode. The conductive agent is carbon black, the binder is PVDF, the mass ratio of the zinc powder negative electrode material, the conductive agent, and the binder is 8:1:1, and the organic solvent is NMP. The drying conditions are preferably a temperature of 80°C and a time of 12 hours. The dried electrode is punched into a circular electrode with a diameter of 12 mm as the negative electrode, copper foil as the positive electrode, a 2 M zinc sulfate solution as the electrolyte, and a glass fiber filter paper as the diaphragm. A zinc-copper half-cell is assembled and subjected to a constant current charge and discharge test. The test results are as follows: Figure 5 As shown, at a current density of 2 mA cm -2 The dough capacity is 2 mAh cm -2 Under the conditions of , the zinc-copper half-cell prepared in Comparative Example 1 only runs for about 24 hours, while the zinc-copper half-cell prepared in Example 3 can stably run for more than 210 hours, and still maintain a high Coulomb efficiency of 99.7% after 110 cycles, showing low cycle fluctuations. This shows that the reversibility of the zinc negative electrode during the electroplating / stripping process can be significantly improved by preferentially exposing the (002) crystal plane through crystal plane regulation.
[0046] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a zinc powder negative electrode material with (002) crystal plane orientation, characterized in that: The following steps are involved: After mixing zinc powder and a grinding aid, ball milling is performed in an inert atmosphere to obtain a mixed powder; The mixed powder is annealed in an inert atmosphere to obtain a zinc powder negative electrode material with a (002) crystal plane orientation.
2. The method for preparing a zinc powder negative electrode material with (002) crystal plane orientation according to claim 1, characterized in that: The ball-to-material ratio of the ball milling treatment is (4-10):1; the rotation speed of the ball milling treatment is 200-500 r / min, and the time is 4-16 hours.
3. The method for preparing a zinc powder negative electrode material with (002) crystal plane orientation according to claim 1, characterized in that: The grinding aid is one or more of stearic acid, calcium stearate, zinc stearate, polyvinyl alcohol and polyethylene glycol.
4. The method for preparing a zinc powder negative electrode material with (002) crystal plane orientation according to claim 1, characterized in that: The amount of the grinding aid is 1-10wt% of the mass of the zinc powder.
5. The method for preparing a zinc powder negative electrode material with (002) crystal plane orientation according to claim 1, characterized in that: The type of the zinc powder is spherical zinc powder.
6. The method for preparing a zinc powder negative electrode material with (002) crystal plane orientation according to claim 1, characterized in that: The inert atmosphere is one of a nitrogen atmosphere, a helium atmosphere or an argon atmosphere.
7. The method for preparing a zinc powder negative electrode material with (002) crystal plane orientation according to claim 1, characterized in that: The parameters of the annealing process are: The heating rate is 5~10℃ / min, the annealing temperature is 300~415℃, and the annealing time is 5~16h.
8. A zinc powder negative electrode material with (002) crystal plane orientation, characterized in that: The (002) crystal plane oriented zinc powder negative electrode material is prepared by the preparation method described in any one of claims 1 to 7.
9. Use of the zinc powder negative electrode material with (002) crystal plane orientation as claimed in claim 8 in aqueous zinc ion batteries.
10. The use of the zinc powder negative electrode material with (002) crystal plane orientation in an aqueous zinc ion battery according to claim 8, characterized in that: Compared with traditional zinc powder negative electrode materials, the cycle life of the aqueous zinc ion battery is increased by two to three times.
Citation Information
Cited By
Preparation method and application of metal interface layer coated zinc powder negative electrode
CN120300153A